RHYTHM DISORDERS IN PATIENTS WITH CHRONIC KIDNEY DISEASE RECEIVING HEMODIALYSIS TREATMENT - Salyamova Feruza Erkinovna (Modern American Journals, 2025)
Cardiovascular diseases are one of the most significant predictors of mortality in patients with end-stage renal disease treated with chronic hemodialysis, and cause at least a third of all hospitalizations [Eisner D. et al., 2001; Johnston N. et al., 2008]. According to the US Renal Disease Registry, the five-year survival rate in the general population of patients on hemodialysis is 33.4% [U. S. Renal Data System, 2009]. More than half of the deaths of patients on renal replacement therapy are due to cardiovascular pathology, the mortality from which in patients on hemodialysis is 30-35 times higher compared to the general population [Zavy A.S. et al., 1998; Herzog S.A., 2003; U.S. Renal Data System, 2009]. A significant proportion of deaths in patients with end-stage renal disease receiving hemodialysis treatment are attributed to those associated with coronary heart disease [Foley R.N. et al., 1998a; Sarnak M.J. et al., 2003; Cheung A.K. et al., 2004]. The theoretical method of research was used. Many articles and dissertations by international scientists were analyzed, which were based on various books, dissertations, as well as electronic journals.
Keywords: Hemodialysis, renal failure, coronary heart disease, arrhythmia.